PENGGUNAAN METODE SQ3R DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MEMBACA PEMAHAMAMAN SISWA KELAS XI SMA NEGERI 12 PEKANBARU - Raja Usman (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2015)
This study is a quasi experimental study aimed to describe the use of methods SQ3R and motivation and student learning outcomes learning materials reading comprehension. Implementation of the research in accordance with the learning procedure starting from planning, core activities and weekend activities. This study is an experimental research that distinguishes SQ3R method and conventional methods as well as motivation and learning outcomes. Research subjects a class XI student of SMAN 12 Pekanbaru. Results motivation and learning outcomes that motivated the data analysis methods SQ3R average of 129.56 and an average of 119.11 conventional methods; (2) Analysis of the average data overall learning outcomes of the students taught using methods SQ3R of 26.56 and 22.33 for the conventionalmethod difference 4.23; (3) Analysis of average data results that are taught using methods SQ3R highest score 30.67 High Group and group the highest score 22.24 Low 8.23 difference in numbers; average data analysis of learning outcomes are taught with methods SQ3R study group Low highest score 26.28 and Conventional High group scores highest score group low 26.28 and the lowest scoring average 18.39 7.89 difference in numbers. So from this analysiscan be concluded that the method SQ3R motivation and learning outcomes is higher than the motivation and learning outcomes conventional methods.